Functional Segregation of the Middle Temporal Visual Motion Area Revealed With Coactivation-Based Parcellation - Gao, Jingjing; Zeng, Min; Dai, Xin; Yang, Xun; Yu, Haibo; Chen, Kai; Hu, Qingmao; Xu, Jinping; Cheng, Bochao; Wang, Jiaojian (Frontiers in Neuroscience, 2020)
Traditionally, the visual motion area (MT) is considered as a brain region specialized for visual motion perception. However, accumulating evidence showed that MT is also related to various functions, suggesting that it is a complex functional area and different functional subregions might exist in this area. To delineate functional subregions of this area, left and right masks of MT were defined using meta-analysis in the BrainMap database, and coactivation-based parcellation was then performed on these two masks. Two dorsal subregions (Cl1 and Cl2) and one ventral subregion (Cl3) of left MT, whereas two dorsal-anterior subregions (Cl1 and Cl2), one ventral-anterior subregion (Cl3), and an additional posterior subregion (Cl4) of right MT were identified. In addition to vision motion, distinct and specific functions were identified in different subregions characterized by task-dependent functional connectivity mapping and forward/reverse inference on associated functions. These results were not only in accordance with the previous findings of a hemispheric asymmetry of MT, but also strongly confirmed the existing of sub-regions in this region with distinct and specific functions. Furthermore, our results extend the special role of visual motion perception on this area and might be facilitate future cognitive study.